Awareness and use of electronic databases as determinants of research productivity of academic staff in Nigerian private universities. Issue 6 (5th October 2018) - Adetomiwa, Basiru; Okwilagwe, Andrew Oshiotse
Abstract : Purpose: The quality of teaching, research and community service of lecturers coupled with their publication in any university system may depend on the quality of the electronic database they use. Electronic database awareness use is very important to the teaching, research and community service activities of lecturers in the Nigerian university system. It has been established that lack of awareness is the main factor militating against effective use of electronic databases. The study aims to investigate awareness and use of electronic databases as determinants of research productivity of academic staff in private universities in South-West Nigeria. Design/methodology/approach: The descriptive survey research design of the correlational type was adopted. Out of the 27 private universities established and approved between 1999 and 2012 in South-West Nigeria, 21 were purposively covered in the study. The stratified random sampling technique based on probability proportionate to size method was adopted in selecting 1, 656 (60 per cent) academic staff from the population size of 2, 760. The main research instrument used to collect data for the study was questionnaire. Data generated were analysed using descriptive and inferential statistics. Spearman's rank was used to test hypothesis at 0.05 level of confidence. Findings: There was a significant positive correlation between awareness and utilisation of electronic databases ( r = 0.690; p < 0.05).The result of the analysis showed that there was average level of awareness of electronic databases among academic staff in private universities in South-West, Nigeria. Research Limitations/Implications: The study selected 21 out of the 27 private universities established and approved between 1999 and 2012 in South-West, Nigeria. Originality/value: Based on the findings, the paper recommends increased investment in ICT facilities at the surveyed universities in line with the emerging digital trend in universities around the world to raise the level of awareness of electronic databases utilisation by academic staff in research.